Who Will Speak for the Water and the Wildlife Conservation? Solving the Problems of Sustainable Development through Cause-related Marketing - Singh, Akansha; Pathak, Govind Swaroop (Problemy Ekorozwoju, 2020)
CRM is adopted by organizations as a viable business strategy to implement sustainability initiatives. The existing literature suggests the variations in the execution style of the CRM campaigns by various organizations. This study proposes Cause-related Marketing (CRM) as one of the novel approaches to combat various issues related to sustainable development. The present study is focused to understand the role of CRM in aiding private sector organizations to address the problems of sustainable development and thus support the ‘United Nations Sustainable Development Goals (SDGs)’ in an Emerging Economy India. The study attempts to integrate the various areas of focus of the CRM campaigns, the sustainability dimensions focused and the various SDGs supported. Further implications, limitations and future research directions have been discussed.